The Effectiveness of a Proposed Blended-learning Model in Developing Literary ‎Translation Skills of Saudi-University Students - Nasr, Mahmoud (Jordan Journal of Educational Sciences, 2022)
The purpose of this study was to design a blended-learning model and to test its effectiveness in developing literary translation skills of Saudi university students. Participants in the study comprised 140 students (including males and females) distributed randomly between the experimental and control groups. Statistical analysis of the data indicated that there were statistically significant differences between the mean scores of the two groups in the post-administration of the test in favor of those of the experimental group. No significant differences were found between the mean scores of males and females in the experimental group in the post-administration of the test. The suggested model proved to be effective in developing literary translation skills of Saudi university students